2000
DOI: 10.1161/01.cir.101.10.1152
|View full text |Cite
|
Sign up to set email alerts
|

Peak Oxygen Uptake Better Predicts Outcome Than Submaximal Respiratory Data in Heart Transplant Candidates

Abstract: Background-Many studies have focused on the prognostic power of peak oxygen uptake (V O 2 ) in patients with chronic heart failure, but maximal exercise testing is not without risk. The purpose of the present study was, therefore, to assess the prognostic significance of the steepness of changes in ventilation and carbon dioxide output (V CO 2 ) during submaximal exercise in comparison with V O 2 . Methods and Results-The study population consisted of 284 adult heart transplant candidates who performed a grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 27 publications
1
46
0
3
Order By: Relevance
“…Previous studies have showed that peak oxygen uptake (VO 2 ) obtained at maximal exercise provides not only an objective measure of functional capacity, but also prognostic information in patients with CHF. [9][10][11][12][13][14] We predict that patients with exercise intolerance are those with higher neurohormonal and cytokine activation, however, the relation between peak VO 2 and multiple neurohormone/cytokine levels has not been clearly elucidated. Thus, we conducted the present study to clarify the relation between neurohormonal/cytokine activation and functional capacity as measured by cardiopulmonary exercise testing in patients with mild to moderate CHF.…”
mentioning
confidence: 99%
“…Previous studies have showed that peak oxygen uptake (VO 2 ) obtained at maximal exercise provides not only an objective measure of functional capacity, but also prognostic information in patients with CHF. [9][10][11][12][13][14] We predict that patients with exercise intolerance are those with higher neurohormonal and cytokine activation, however, the relation between peak VO 2 and multiple neurohormone/cytokine levels has not been clearly elucidated. Thus, we conducted the present study to clarify the relation between neurohormonal/cytokine activation and functional capacity as measured by cardiopulmonary exercise testing in patients with mild to moderate CHF.…”
mentioning
confidence: 99%
“…There is ongoing debate whether submaximal CPET results are prognostically useful. 9,24 Even if the subgroup of patients with reduced exercise tolerance could have generated submaximal peak VO 2 values, they do reproduce valid VE/VCO 2 slopes. 8 We therefore did not exclude patients with short-lasting, possibly submaximal, exercise tests.…”
Section: Study Limitationsmentioning
confidence: 99%
“…[1][2][3][4] By contrast, recent studies have shown that a low PP carries a worse prognosis in patients with advanced chronic heart failure (CHF) 5,6 and decompensated heart failure, 7 which is attributed to the fact that the impaired LV function has become the major determinant of PP. However, peak oxygen uptake (VO 2 peak), which is a major if not the major prognostic factor in CHF 8,9 was not considered in these studies. Our aim was therefore to analyse whether PP adds prognostic precision to VO 2 peak in patients with advanced CHF, who were referred to our centre for assessment of their suitability for heart transplantation (HTX) between May 1991 and December 1996 and who performed a graded symptom-limited bicycle exercise test with measurement of respiratory gas analysis, including VO 2 peak.…”
mentioning
confidence: 99%
“…Our aim was therefore to analyse whether PP adds prognostic precision to VO 2 peak in patients with advanced CHF, who were referred to our centre for assessment of their suitability for heart transplantation (HTX) between May 1991 and December 1996 and who performed a graded symptom-limited bicycle exercise test with measurement of respiratory gas analysis, including VO 2 peak. 9 Blood pressure (BP) was measured by the auscultatory technique using the STBP-78 device (Colin, Komaki, Japan) or directly by trained investigators, at rest in the sitting position before the exercise test. PP was calculated as the difference between systolic and diastolic BP, and mean BP as diastolic BP plus one-third of PP.…”
mentioning
confidence: 99%
See 1 more Smart Citation